2015
DOI: 10.3109/14764172.2014.1003243
|View full text |Cite
|
Sign up to set email alerts
|

Striae after topical corticosteroid: Treatment with nonablative fractional laser 1540nm

Abstract: Striae distensae are atrophic dermal scars associated with psychosocial stress. Several treatments have been used but there is no gold standard until now. Fractional photothermolysis has been described as a successful and safe method to treat scars. In this description, we report 4 patients (Fitzpatrick phototype IV) who developed striae distensae after long-term use of topical corticosteroids and were successfully treated with fractional nonablative 1540 nm Erbium: glass laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The absorption of this wave length in the microvasculature within the dermal papillae and dermis increases the temperature around the vessels producing a thermal damage su cient to stimulate the different phases of wound healing, and causing collagen remodeling. 5 Moreover, LP Nd: YAG laser provokes a new collagen formation potentiating the improvement of SD [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of this wave length in the microvasculature within the dermal papillae and dermis increases the temperature around the vessels producing a thermal damage su cient to stimulate the different phases of wound healing, and causing collagen remodeling. 5 Moreover, LP Nd: YAG laser provokes a new collagen formation potentiating the improvement of SD [14].…”
Section: Discussionmentioning
confidence: 99%
“…The 1064 nm long-pulsed (LP) Nd: YAG laser increased the dermal collagen when utilized in the treatment of atrophic scars and facial wrinkles. Additionally, ND: YAG laser has a powerful a nity to vascular chromophores, so it can be used effectively in treating striae rubra [5]. Therefore, the objective of this work was to compare and evaluate the effect of 1,064 nm LP Nd: YAG laser and fractional CO2 laser clinically and histologically in managing SD.…”
Section: Introductionmentioning
confidence: 99%
“…9 Cushing syndrome or long term administration of topical/oral corticosteroids may cause the developing of striae. 5,[10][11][12][13] Genetic susceptibility can definitely have a major role as well; however, the precise mechanism has not completely elucidated. Tung et al performed some accurate genome analysis and demonstrated the collapse of elastic microfibrils as the etiology of some cases of striae distensae.…”
Section: Introductionmentioning
confidence: 99%
“…[233435] The laser (1550 nm) has shown to reduce dimensions of SD with improved elasticity, colour and skin texture; when used by multiple investigators in different striae like SG,[36] breast striae post-augmentation surgery[37] and steroid-induced striae. [38] Stotland et al has reported overall improvement in dimensions of SD independent of age, gender and skin phototype with the use of 1550 nm, erbium-doped fibre laser; but lesser improvement in dyschromia and texture of striae. [39] Most common adverse events were transient pain, post-treatment erythema, oedema and dyschromia.…”
Section: Non-ablative Lasersmentioning
confidence: 99%